(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Third gender persons had been part of Indian society for centuries. There was historical evidence of recognition of third gender in the writings of ancient India. The concept of thritiyaprakriti or napumsaka had been an integral part of the Hindu mythology, folklore, epics and early vedic and puranic literature. Third gender people occupied a niche position and sometimes enjoying unique benefits. Many cultures and mythologies worldwide since ages have mentioned and discussed the existence of androgyny in addition and equivalence to the existence of male and female genders. Androgyny refers to the existence of both male and female characteristics as well as anatomy in the same body or person. An androgynous body is a definite kind of body that contains both female and male organs and hence cannot be classified as eithermale or female and is considered intersex and ambiguous.